ANALISIS PENGARUH MOTIVASI KERJA DAN ETIKA KERJA PADA KINERJA KARYAWAN DENGAN MASA KERJA SEBAGAI VARIABEL MODERASI - Alwi Suddin, Jaka Parwanta & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2015)
The research objectives are to analyze the significance of the effect work motivation on employee performance, work ethics on employee performance, tenure on employee performance, the effect of the work motivation on employee performance moderated by tenure, and the effect of the work ethic on employee performance moderated by tenure in Business Multi Purpose Cooperative Sinar Mas Motor Delanggu. The research method used survey method, the type of data use quantitative and qualitative data. Source of data used are primary and secondary data. Collection method: questionnaires, interviews, and observations. The sampling technique to include all employees by 30 respondents. Test instrument is validity and reliability test. Data analysis technique used classic assumption test, multiple linear regression analysis, t test, f test, and the coefficient of determination (R2), the absolute value of the difference test. The test result indicates that motivation (X1) have an influence on employee performance (Y) in the Business Multipurpose Cooperative Sinar Mas Motor Delanggu because the value of the regression of the most large. The tenure does not moderate the effect of work motivation on employee performance and the tenure does not moderate influence on employee performance work ethic in Multipurpose Cooperative Sinar Mas Motor Delanggu. Keywords: work motivation, work ethic, tenure and performance